2019
DOI: 10.1002/aoc.4741
|View full text |Cite
|
Sign up to set email alerts
|

Oxime palladacycle in PEG as a highly efficient and recyclable catalytic system for phenoxycarbonylation of aryl iodides with phenols

Abstract: In this report, we have developed a sustainable protocol for the synthesis of aromatic esters by a carbonylative method using di‐μ‐chlorobis [5‐hydroxy‐2‐[1‐(hydroxyimino‐ĸN) ethyl] phenyl‐ĸC] palladium (II) dimer (1) catalyst in PEG‐400 as a greener and recyclable solvent. The reaction is carried out at room temperature using CO in a balloon. Good to excellent yield of various esters can be synthesize using this protocol. Direct insertion of CO moiety leads to the high atom and step economy. Compared to previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This catalytic system employs the utilization of either solid CO or CO gas surrogates, such as Cr(CO) 6 , Co 2 (CO) 8 , and Nformyl saccharin, with the addition of Pd ligands. [12][13][14][15][16][17][18][19] Although these methodologies exhibited excellent catalytic activity for carbonylative esterification reactions, drawbacks such as additional requirements of co-catalyst, subpar solubility, demanding conditions, and restricted applicability, especially for the use of toxic CO gas, further limit their application. In addition, since the reported Ni(CO) 4 -catalyzed carbonylation reaction by Bauld, significant progress has been reported in exploring nickel-catalyzed coupling reactions involving aryl halides and phenols, 20 whereas Bhanage demonstrated nickelcatalyzed carbonylation reactions involving alcohols and aryl halides with o-chlorophenyl formate as a safer alternative to directly employing the highly toxic CO gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This catalytic system employs the utilization of either solid CO or CO gas surrogates, such as Cr(CO) 6 , Co 2 (CO) 8 , and Nformyl saccharin, with the addition of Pd ligands. [12][13][14][15][16][17][18][19] Although these methodologies exhibited excellent catalytic activity for carbonylative esterification reactions, drawbacks such as additional requirements of co-catalyst, subpar solubility, demanding conditions, and restricted applicability, especially for the use of toxic CO gas, further limit their application. In addition, since the reported Ni(CO) 4 -catalyzed carbonylation reaction by Bauld, significant progress has been reported in exploring nickel-catalyzed coupling reactions involving aryl halides and phenols, 20 whereas Bhanage demonstrated nickelcatalyzed carbonylation reactions involving alcohols and aryl halides with o-chlorophenyl formate as a safer alternative to directly employing the highly toxic CO gas.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported studies have demonstrated carbonylative esterification reactions catalyzed by Pd(II) complexes, such as Pd(OAc) 2 /PPh 3 10 and PdCl 2 (PhCN) 2 , 11 in conjunction with ferrocenyl phosphine ligands (Scheme 1b). This catalytic system employs the utilization of either solid CO or CO gas surrogates, such as Cr(CO) 6 , Co 2 (CO) 8 , and N ‐formyl saccharin, with the addition of Pd ligands 12–19 . Although these methodologies exhibited excellent catalytic activity for carbonylative esterification reactions, drawbacks such as additional requirements of co‐catalyst, subpar solubility, demanding conditions, and restricted applicability, especially for the use of toxic CO gas, further limit their application.…”
Section: Introductionmentioning
confidence: 99%
“…This transformation implies an essential synthetic process in both synthetic chemistry and industry. [5][6][7] In the last few years, phenoxy carbonylation reactions were reported using aryl halide with phenol in the presence of palladium catalyst using CO gas or solid CO surrogate including Co 2 (CO) 8 , Cr (CO) 6 , and N-formyl saccharine in the presence of palladium catalysts with ligands. [8][9][10] Despite these methodologies being excellent for carbonylative esterification reactions, there are some limitations to the use of expensive palladium catalysts, with additional requirements of moisture-sensitive ligands, co-catalyst, additives, and the handling of CO gas.…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of such reactions, Pd­(II)-catalyzed carbonylation for the synthesis of aromatic esters, such as Pd­(OAc) 2 /PPh 3 and PdCl 2 (PhCN) 2 with ferrocenyl phosphine ligands, has been reported . This transformation involves the use of CO gas or solid CO surrogates such as Cr­(CO) 6 , Co 2 (CO) 8 , and N -formyl saccharine in the presence of the Pd-ligand catalytic system (Scheme b). Although the carbonylative esterification reactions occurred efficiently, there are some limitations such as additional requirements of cocatalysts, moisture-sensitive ligands, and additives, especially for reactions involving the use of CO gas that require special precautions because of its highly toxic nature. Additionally, nickel-catalyzed carbonylation of aryl halides with alcohols has also been developed since Bauld reported such reactions under Ni­(CO) 4 catalysis .…”
Section: Introductionmentioning
confidence: 99%